Glyoxal‐induced formation of advanced glycation end‐products in type 1 collagen decreases both its strength and flexibility in vitro. Issue 9 (11th March 2021) - Kitamura, Kei‐ichiro; Hirayama, Jun; Tabuchi, Yoshiaki; Minami, Takao; Matsubara, Hajime; Hattori, Atsuhiko; Suzuki, Nobuo
Abstract: The high plasma glucose induced in glucose metabolism disorders leads to the non‐enzymatic glucose‐dependent modification (glycation) of type 1 collagen, which is an essential component of bone tissue. The glycation of proteins induces the formation of advanced glycation end‐products, such as carboxymethyl arginine, which is preferentially generated in glycated collagen. However, the effect of advanced glycation end‐product formation on the characteristics of type 1 collagen remains unclear due to the lack of suitable in vitro experimental systems analyzing type 1 collagen. Here, we show that the glycation of type 1 collagen can be analyzed in vitro using a goldfish‐scale bone model. Our study using these scales provides evidence that the advanced glycation end‐product formation in type 1 collagen induced by glyoxal, the carboxymethyl arginine inducer, facilitates the crosslinking of type 1 collagen, decreasing both its strength and flexibility. Abstract : Here we show that the glycation of type 1 collagen can be analyzed in vitro using a goldfish‐scale bone model. Our study using these scales provides evidence that glycation of type I collagen alpha chains facilitates the crosslinking of type I collagen, decreasing both its strength and flexibility.